Sodium channels induced by depolarization of the Xenopus laevis oocyte. - Baud, C (1982)
An electrically gated Na+ channel can be made to appear in the membrane of the Xenopus laevis oocyte by simple depolarization. This membrane normally responds passively to imposed transmembrane currents with resting potentials around -60 mV, but when it is held depolarized to more than about +30 mV it becomes possible to obtain long-lasting regenerative depolarizations up to +80 mV; these depolarizations can last as long as 20 min. This potential is due to an "induction" of a Na+-dependent channel that is electrically gated open and closed. Its threshold for opening is about -20 mV and it is selective for Na+ over Cs+ and choline+ but is blocked by relatively small quantities of Li+. When a long voltage clamp step to a positive potential under ENa (+70 to +90 mV) is applied, an inward current is observed for many minutes, implying that this channel does not have an inactivation mechanism. The inward Na+ current is blocked by 0.50 mM tetrodotoxin. When the membrane is held at or near resting potential, the excitability will disappear with time, but it can be made to reappear by again depolarizing the membrane.